ANALISIS KESULITAN SISWA DALAM PEMECAHAN MASALAH MATEMATIK SISWA SMP PADA MATERI TEOREMA PHYTAGORAS - Nissa Risma Mulyanti; Nur Yani; Risma Amelia (IKIP Siliwangi, 2018)
This article an analysis of the results of the test about problem-solving mathematical of grade IX students of Junior High School. This analysis aims to know the kinds of difficulties experienced by students and to determine the level of problem-solving skills students in the mathematics of junior high school students in Cimahi City. The research method used is qualitative descriptive. The samples taken for this research are 37 students of class IX in one of junior high school in Cimahi City. Instrument test of the problem-solving ability of mathematics given as many as 5 item. The results of the analysis obtained based on written tests conducted is the level of ability problem-solving mathematics students in one of junior high school in Cimahi is still relatively low.